Competition Policy, Consumer Protection, and Economic Disadvantage - William E. Kovacic (Washington University Journal of Law & Policy, 2007)
This Essay discusses how well-conceived competition policies can serve the poor and reduce barriers that reinforce economic disadvantage. It first identifies some of the phenomena that competition policy programs usefully can address to improve the welfare of economically disadvantaged populations. The Essay then describes how consumer protection programs can complement competition policy measures by punishing and deterring serious fraud. The Essay concludes with reflections on the broader contributions to social welfare that competition and consumer protection programs can offer. In addressing these topics I have sought to draw upon examples from my own experiences in the United States and in technical assistance projects.
Keywords: Public welfare; Poverty; Consumer protection; Antitrust law; Social justice; Competition (Economics); Economic development; China; United States; Vietnam